RNAseq Analysis of the Response of Arabidopsis thaliana to Fractional Gravity Under Blue-Light Stimulation During Spaceflight - Herranz, Raúl; Vandenbrink, Joshua P.; Villacampa, Alicia; Manzano, Aránzazu; Poehlman, William L.; Feltus, Frank Alex; Kiss, John Z.; Medina, Francisco Javier (Frontiers in Plant Science, 2019)
Traveling to nearby extraterrestrial objects having a reduced gravity level (partial gravity) compared to Earth’s gravity is becoming a realistic objective for space agencies. The use of plants as part of life support systems will require a better understanding of the interactions among plant growth responses including tropisms, under partial gravity conditions. Here, we present results from our latest space experiments on the ISS, in which seeds of Arabidopsis thaliana were germinated, and seedlings grew for six days under different gravity levels, namely micro-g, several intermediate partial-g levels, and 1g, and were subjected to irradiation with blue light for the last 48 hours. RNA was extracted from 20 samples for subsequent RNAseq analysis. Transcriptomic analysis was performed using the HISAT2-Stringtie-DESeq pipeline. Differentially expressed genes were further characterized for global responses using the GEDI tool, gene networks and for Gene Ontology (GO) enrichment. Differential gene expression analysis revealed only one differentially expressed gene (AT4G21560, VPS28-1 a vacuolar protein) across all gravity conditions using FDR correction (q<0.05). However, the same 14 genes appeared differentially expressed when comparing either micro-g, low-g level (<0.1g) or the Moon g-level with 1g control conditions. Apart from these 14-shared genes, the number of differentially expressed genes was similar in microgravity and the Moon g-level and increased in the intermediate g-level (<0.1g), but it was then progressively reduced as the difference with the Earth gravity became smaller. The GO groups were differentially affected at each g-level: light and photosynthesis GO under microgravity, genes belonged to general stress, chemical and hormone responses under low-g, and a response related to cell wall and membrane structure and function under the Moon g-level. Transcriptional analyses of plants under blue light stimulation suggests that root blue-light phototropism may be enough to reduce the gravitational stress response caused by the lack of gravitropism in microgravity. Competition between tropisms induces an intense perturbation at the micro-g level, which shows an extensive stress response that is progressively attenuated. Our results show a major effect on cell wall/membrane remodeling (detected at the interval from the Moon to Mars gravity), which can be potentially related to graviresistance mechanisms.